An introduction to mathematics for engineers [ mechanics - Lee (London: Hodder Education, 2008)
Minimum System Requirements for CD-ROM: Microscoft Windows 2000 or XP; 510 MB ram; 200 MB hard disk space; screen resolution 800 x 600 or higher; 12x CD-ROM driver (or faster)
To accompany textbook titled "An introduction to mathematics for engineers : mechanics / Stephen Lee"
FOEAT
Keywords: Engineering mathematics